2019
DOI: 10.1590/0102-311x00031418
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic inequalities in the consumption of fruits and vegetables: Colombian National Nutrition Survey, 2010

Abstract: The objective of this study was to estimate inequalities in the consumption of fruits and vegetables. A multilevel study was performed based on cross-sectional data of adults from 18 to 64 years of age (n = 5,217) and in geodemographic units (n = 33). The consumption of fruits and vegetables was estimated with a food frequency questionnaire administered as part of the 2010 Colombian National Nutrition Survey (ENSIN). Inequality indices for the consumption of whole fruits and fruit juice and for raw and cooked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
(55 reference statements)
2
5
0
2
Order By: Relevance
“…In addition, the Colombian adolescents had low overall fruit and vegetable consumption, despite having increased their fruit intake in a significant way during confinement. These results are consistent with previous studies that show that the Colombian population does not consume the recommended amount of fruits and vegetables [31]. In our study, Spain and Italy were the countries with the greatest mean consumption of fruits (4-5 times per week), and significantly increased their consumption during COVID-19 confinement (Table 2).…”
Section: Countrysupporting
confidence: 93%
“…In addition, the Colombian adolescents had low overall fruit and vegetable consumption, despite having increased their fruit intake in a significant way during confinement. These results are consistent with previous studies that show that the Colombian population does not consume the recommended amount of fruits and vegetables [31]. In our study, Spain and Italy were the countries with the greatest mean consumption of fruits (4-5 times per week), and significantly increased their consumption during COVID-19 confinement (Table 2).…”
Section: Countrysupporting
confidence: 93%
“…A first step would be to identify an association between income inequality and dietary behavior, such as fruit and vegetable intake. In a recent study, researchers did not observe a significant relationship between income inequality and fruit and vegetable intake but these findings were observed among adults in Colombia [25]. Income inequality might be adversely associated with fruit and vegetable intake among adults living in higher socioeconomic countries.…”
Section: Introductionmentioning
confidence: 88%
“…It has been consistently found that the prevalence of fruit and vegetable consumption was positively associated with socio-economic level [ 34 ]. In our study, an equitable consumption of DGLV was seen, but vitamin A-rich fruits and vegetables were socio-economically, disproportionately distributed.…”
Section: Discussionmentioning
confidence: 99%